Female Cosmetic in Unani Medicine, A Literary Review. - Farzana, M.U.Z.N.; Fahamiya, N.; Shiffa, M.S.M. (Gampaha Wickramarachchi Ayurveda Institute, 2016)
Cosmetics are substances used to enhance or protect the appearance or odour of the human body...
Keywords: Cosmetics; Unani medicine; Herbal cosmetics